Estratégias de Educação Ambiental em parques e praças urbanas para mitigar a Impercepção Botânica: Uma revisão integrativa da literatura - Alves, Graziele Almeida (Universidade Federal de São Carlos, 2025)
Botanical imperception—here understood as the difficulty in noticing and valuing plants and corresponding to what international literature terms Plant Awareness Disparity (Parsley, 2020)—remains a challenge in science education, particularly in urban contexts. This study aims to analyze educational strategies linked to science teaching that use urban parks and squares as didactic resources to mitigate this phenomenon. An integrative literature review was conducted following the stages proposed by Souza, Silva, and Carvalho (2010). Six studies published between 2015 and 2025 were selected, describing practices developed in urban non-formal environments, including interpretive trails, didactic sequences, floristic surveys, and the use of digital technologies. The results indicate that multisensory, socioculturally situated strategies with teacher mediation foster greater engagement with local flora, while interventions restricted to visual observation show limitations in overcoming zoocentrism. We conclude that parks and squares constitute powerful pedagogical spaces for promoting plant perception and strengthening science education in urban environments.
Strategies for environmental education in urban parks and squares to mitigate Plant Blindness: An integrative literature review
Keywords: Impercepção botânica; Educação ambiental; Espaços não formais; Parques urbanos; Botanical imperception; Environmental education; Non-formal spaces; Urban parks; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade